Contrasting patterns of turnover between plants, pollinators and their interactions - Norfolk, Olivia; Eichhorn, Markus P.; Gilbert, Francis S. (Wiley, 2015)
Aim: Biogeographers typically assess patterns of diversity across landscapes. As interacting groups often exhibit contrasting trends, this leads to variation in the structure of interaction networks and thereby influences ecosystem processes. Here we aim to disentangle how patterns of diversity differ between species (plants, pollinators) and their interactions across an agricultural landscape. The region is known for its irrigated gardens which appear as high-diversity islands in the mountainous habitat. We are interested in whether this local enhancement was (a) increasing landscape heterogeneity by supporting novel species or (b) increasing local diversity by supporting higher densities of species that also occur in the unmanaged habitat. Location: South Sinai, Egypt. Methods: We compared alpha diversity of plants, pollinators and interactions in agricultural gardens and plots of unmanaged habitat in two altitudinal categories, high and low mountains, with high and low habitat quality in the matrix respectively. We then used similarity analyses involving the CqN measure to compare levels of turnover across the landscape. Results: The impact of the gardens differed with respect to the landscape context; in the low mountains, gardens enhanced the abundance and diversity of plants, pollinators and interactions, but in the high mountains, they had no effect. Plants exhibited high levels of turnover, with gardens increasing heterogeneity by supporting novel crop species. In contrast, pollinators exhibited low levels of turnover, with gardens and unmanaged habitat supporting similar species. The diversity of interactions was influenced by the composition of the plant community and showed extremely high levels of turnover. Main conclusions: Plants, pollinators and their interactions can display contrasting patterns of turnover across a shared landscape. Although the enhancement of local habitat can boost pollinator diversity, the maintenance of habitat heterogeneity may also be required if you aim to conserve the diversity of interactions between plants and pollinators.